Altered Microbiota Diversity and Bile Acid Signaling in Cirrhotic and Noncirrhotic NASH-HCC. Issue 3 (4th March 2020) - Sydor, Svenja; Best, Jan; Messerschmidt, Insa; Manka, Paul; Vilchez-Vargas, Ramiro; Brodesser, Susanne; Lucas, Christina; Wegehaupt, Annemarie; Wenning, Chiara; Aßmuth, Sophia; Hohenester, Simon; Link, Alexander; et al.
Abstract : OBJECTIVES: The precipitous increase in nonalcoholic steatohepatitis (NASH) is accompanied by a dramatic increase in the incidence of NASH-related hepatocellular carcinoma (HCC). HCC in NASH has a higher propensity to arise without pre-existing cirrhosis compared with other chronic liver diseases. METHODS: To identify the potential links between liver and gut in NASH-related hepatocarcinogenesis, we compared the gut microbiota and mediators of bile acid (BA) signaling in the absence or presence of cirrhosis through the analysis of stool and serum samples from patients with NASH non-HCC and NASH-HCC and healthy volunteers. RESULTS: Serum levels of total and individual BA were higher in NASH compared with healthy controls. Furthermore, serum levels of the primary conjugated BAs glycine-conjugated cholic acid, taurine-conjugated cholic acid, glycine-conjugated chenodeoxycholic acid, and taurine-conjugated chenodeoxycholic acid were significantly increased in cirrhotic vs noncirrhotic patients, independent of the occurrence of HCC. By contrast, serum FGF19 levels were higher in patients with NASH-HCC and associated with tumor markers as well as an attenuation of BA synthesis. Specific alterations in the gut microbiome were found for several bacteria involved in the BA metabolism including Bacteroides and Lactobacilli. Specifically, the abundance of Lactobacilli was associated with progressive disease, serum BA levels, and liver injury in NASH and NASH-HCC. DISCUSSION: Here, we demonstrate a clear association of the altered gut microbiota and primary conjugated BA composition in cirrhotic and noncirrhotic patients with NASH-HCC. Microbiota-associated alterations in BA homeostasis and farnesoid X receptor signaling, via FGF19, might thus contribute to fibrogenesis, liver injury, and tumorigenesis in NASH-HCC.